Operational naval logistics - Eccles, Henry E. (Henry Effingham) 1898-1986 (Theater of operations, 2003)
"Operational Naval Logistics is devoted to the thesis that while we must expect to make new mistakes in the logistics of a future war, we should not repeat the old ones. It is a philosophical approach to the study of logistics as a command responsibility and it is dedicated to the principle that the cost of military operations can be reduced by the avoidance of past mistakes, by the adherence to proven methods and techniques, and by the conscious, unremitting effort on the part of everyone to improve the operating efficiency of our logistic support systems. In peace or war, or in the shadowy vale which lies between the two, the answer to the question of how much logistic support should be provided for an operation must always be "No more than absolutely necessary.""The object of Operational Naval Logistics is to challenge its readers to find better, cheaper, more efficient ways of supporting military operations. If it results in a single worthwhile saving being made, or a single better, more efficient technique being devised, it will have been well worth the effort and expense of its publication." -- D. B. BearyVice Admiral, United States NavyPresident, Naval War College